Theoretical support of modern issues related to laser techniques, applications of coherent radiation and modern technologies - Milesa Srećković; Svetlana Pelemiš; Stanko Ostojć; Sanja Jevtić; Slađana Pantelić; Miloš Đurić; Branka Kaluđerović; Zoran Latinović; Nada Ratković Kovačević (Journal of Engineering & Processing Management, 2021)
Modern problems of the Earth's population are increasing in the areas related to the basic concepts of survival of living beings, but also with opposite views, if parallels are made between energy and ecology. Many new technologies are searching for their way towards development and must be viewed from several points of view. In this paper, the issue is addressed through modern laser techniques in terms of obtaining energy for various purposes concerning selected roles in medicine, as well as the impact on flora, fauna and as a support to other technologies both classical and modern. Contemporary attributes of lasers and other quantum generators in terms of coherence, power and intensity densities have significantly increased, although some predictions from the time of the first quantum generator masers, like gammarasers (and X raser) are still relatively far from commercial concepts. Some of the possible contemporary implementations of quantum generators in measurements control and processing schemes, along with other possible applications of various laser types, have been estimated. The paper focuses on the characterization of today’s problems with Covid-19 virus, only from the engineering point of view. The lexical side of the issue is also included, as well as the social management needs with the application of modern technologies, including help from natural sciences.
Keywords: energy; hardness; laser; scattering; ecology; corona virus